Analisis Faktor-Faktor yang Mempengaruhi Motivasi Belajar pada Anak Usia Dini - Nur Haerani; Fitra Ramadhana; Indar Ridawati; Fitri Anggun Ayudiningsi; Zalsabilah Zalsabilah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aims to analyze the factors that influence learning motivation in early childhood, both from internal and external aspects. The method used is a literature study by reviewing various relevant sources published in the last ten years. The analysis was carried out by comparing and compiling related findings to build a structured framework. The results of the study indicate that early childhood learning motivation is influenced by internal factors such as interest, self-confidence, and physical and mental conditions, as well as external factors such as the role of family, teachers, learning environment, peers, and the impact of digitalization. The family is the main element in shaping children's learning motivation, while teachers and the learning environment play an important role in creating a fun and supportive learning atmosphere. Digitalization, although it has positive potential, can also be a major challenge for children's learning motivation if not managed properly. This study concludes that appropriate intervention from all related parties can increase learning motivation and support the optimal development of early childhood.